สมบัติของไม้ยางพาราอัดสารสกัดจากเปลือกไม้กระถินเทพา - วิศนีย์ ยิ่งประเสริฐ (มหาวิทยาลัยสงขลานครินทร์, 2022)
Researcher was extracted the chemical substances from Acacia mangium bark with distilled water and identified them. The solution of Acacia mangium bark extracts in distilled water was prepared at different concentrations including 5%, 10%, 15% and 20% before vacuum impregnated into rubberwood with the method described in ASTM D 1413-99. The color of rubberwood impregnated with the bark extracts was observed. The retention of the bark extracts on rubberwood was calculated. The anatomy structures, dimension stability, glue ability, decay fungal resistance and subterranean termite resistance of impregnated rubberwood were determined. The results showed that Acacia mangium bark contained as much as 70 volatile organic compounds. The five most abundant substances were: 4-ethynylcyclopentene, nitromethane, 1,2,3-propanetriol, ethyl palmitate and ethyl-octadec-9-enoate. They were found 14.93%, 12.49%, 9.23%, 6.62%, and 3.55% of total contents, respectively. The color of impregnated wood was darker according to the concentration of bark extracts from light brown to red brown and dark brown. The bark extracts can penetrate deeply in to the center of the thickness of wood and remained in the lumen of Vessels, parenchymas and rays cells. However, most of bark extracts were coated on the outer surfaces of wood. If the concentration of bark extracts were 15% and 20%, the dry powders of bark extracts were found on the outer surfaces of wood. The bark extracts can improve the dimension stability of rubberwood. The wood impregnated with bark extracts at the concentration of 10% gave the highest value of ASE (Anti-swelling efficiency) and MEE (Moisture exclusion efficiency). The ASE value of impregnated wood with 10% concentration of bark extracts in the radial, tangential and longitudinal direction were 89.0215.37%, 86.7915.32% and 92.32+7.53%, respectively. The MEE value of impregnated wood with 10% concentration of bark extracts was 58.09+1.76%. The glue ability of impregnated wood was decreased when the retention of bark extracts in wood was increased. However, the glue ability of impregnated wood with 10% concentration of bark extract was significantly similar with the glue ability of non-impregnated ubberwood. The bark extracts had affected on decay fungal (Trametes Versicolor and Gloeophyllum Striatum) resistance of impregnated wood. When the retention of bark extracts in wood was increased the percentage of weight loss of impregnated wood after the decay fungal attack was decreased. The bark extracts may be toxic to termites (Coptotermes gestroi) after they consumed the impregnated wood for a long time. It was observed that termites were died during the third and fourth week after they were attacked the impregnated wood with 15% and 20% concentration of bark extracts. The impregnated wood with 10% concentration of bark extract gave the lowest value of percentage of weight loss, 20.50(+-3.02)%, after 28 days of termite attack. This research can conclude that the 10% concentration of bark extracts was the optimum concentration for vacuum impregnated into rubberwood. It can penetrate deeply into wood and no dry powder of bark extracts adhered on the outer surfaces of wood. It gave the best value of dimension stability and glue ability of impregnated wood. The decay fungal resistance and termite resistance of impregnated wood with 10% of bark extracts are better than that of rubberwood.